2021
DOI: 10.3390/cancers13174343
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Heterogeneity, Therapeutic Hurdle Confronting Sorafenib and Immune Checkpoint Inhibitors in Hepatocellular Carcinoma

Abstract: Despite the latest advances in hepatocellular carcinoma (HCC) screening and treatment modalities, HCC is still representing a global burden. Most HCC patients present at later stages to an extent that conventional curative options are ineffective. Hence, systemic therapy represented by the tyrosine kinase inhibitor, sorafenib, in the first-line setting is the main treatment modality for advanced-stage HCC. However, in the two groundbreaking phase III clinical trials, the SHARP and Asia-Pacific trials, sorafeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 140 publications
0
7
0
Order By: Relevance
“…In addition, an imbalance between anti-apoptotic and pro-apoptotic proteins is associated with sorafenib resistance. Nonetheless, the exact underlying mechanism of sorafenib resistance needs to be further elucidated (112).…”
Section: Drug Resistance Of Combination Therapymentioning
confidence: 99%
“…In addition, an imbalance between anti-apoptotic and pro-apoptotic proteins is associated with sorafenib resistance. Nonetheless, the exact underlying mechanism of sorafenib resistance needs to be further elucidated (112).…”
Section: Drug Resistance Of Combination Therapymentioning
confidence: 99%
“…Recently, a study showed that tremelimumab plus durvalumab (STRIDE) had a median OS of 16.43 months compared to sorafenib with a median OS of 13.77 months in unresectable HCC ( Kudo, 2022 ). However, HCC is a highly heterogeneous cancer with substantial genomic heterogeneity, which influences the cellular response of systemic therapy such as sorafenib and ICIs ( Atwa et al, 2021 ). For patients with resistance to sorafenib (first-line therapy) in advanced HCC, regorafenib (RESORCE), cabozantinib (CELESTIAL), ramucirumab (REACH-2), nivolumab in combination with ipilimumab (CheckMate 040), or pembrolizumab (Keynote 240) were recommended ( Solimando et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of HCC primary resistance to ICIs seems to encompass both tumor intrinsic and micro-environment (TME) levels [14]. Among the former, WNT/CTNNTB1 somatic mutation has the soundest evidence to promote HCC immune escape [15], along with the expression of multiple immune checkpoints such as lymphocyte-activation gene 3 (LAG-3), fibrinogen-like protein1(FGL1), T-cell immunoreceptor with Ig and ITIM domains (TIGIT)-nectin cell adhesion molecule 2 (NECTIN2) and CD 155. Different immune cell populations and epigenetic mechanisms are top players in TME-related resistance to ICIs.…”
Section: Introductionmentioning
confidence: 99%